DIGITAL AND FINANCIAL LITERACY DRIVING MICRO FINANCE ACCESS: RELIGIOSITY AS CATALYST FOR SME DEVELOPMENT - Darda, Ahmad; Yuli, Rama; Wati, Lela Nurlaela; Abdrazakova, Ainur (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2025)
Microfinancing has contributed to the development of micro, small, and medium enterprises (MSMEs), market expansion, and reduced economic inequality in developing countries. Microfinancing enhances MSMEs’ resilience to economic and environmental changes by facilitating the adoption of sustainable technology. Gaps in financial literacy, particularly in financial management, impede MSMEs access to credit. Limited digital literacy and poor Internet access hinder MSMEs engagement in the digital economy. This study analyzes how financial literacy and digital platform usage influence microfinancing and MSMEs development, with religiosity as a moderating factor. Using a quantitative methodology with structural equation modeling and moderating regression analysis, the research sampled 200 MSMEs that obtained loans from formal microfinance institutions, specifically conventional People’s Economic Banks (BPR) and Sharia People’s Economic Banks (BPRS) in Western Indonesia. The results demonstrate that financial literacy and digital platforms facilitate access to microfinance and MSMEs growth, aligning with the theories of Diffusion of Innovation, Technology Acceptance Model, and Resource-Based View. The ineffectiveness of microfinance as a mediating variable reveals a disparity between financing access and productive fund utilization. The negative moderation of religiosity on the effect of financial literacy on microfinancing shows the influence of religious values on MSMEs’ financial perceptions. These results indicate the need to integrate financial literacy, digital mentoring, and religious-value-based strategies into MSME empowerment programs. Financing institutions must modify their interventions to ensure that financing promotes inclusive MSME growth. This study uniquely examines religiosity moderation and microfinancing’s ineffectiveness as mediating factors in MSME digitalization in developing countries.